Comparison of surgical outcomes between iStent inject W implantation and microhook ab interno trabeculotomy in combination with phacoemulsification in primary open-angle glaucoma patients - Onoe, Hiromitsu; Hirooka, Kazuyuki; Namiguchi, Koji; Mizoue, Shiro; Hosokawa, Hiroko; Mochizuki, Hideki; Okada, Naoki; Tokumo, Kana; Okumichi, Hideaki; Kiuchi, Yoshiaki (Frontiers in Medicine, 2023)
Purpose To examine primary open-angle glaucoma patients after undergoing combined cataract surgery with microhook ab interno trabeculotomy (μLOT-Phaco) or iStent inject W implantation (iStent-Phaco), and then evaluate the surgical outcomes after a minimum of 6 months of follow-up. Methods Between October 2020 and July 2022, 39 μLOT-Phaco eyes and 55 iStent-Phaco eyes that underwent surgery were evaluated in this retrospective, multicenter comparative case series. Data that included preoperative and postoperative intraocular pressure (IOP), number of glaucoma medications, and occurrence of complications were collected from medical records and then examined. Surgical failure was defined as patients exhibiting a < 20% reduction in the preoperative IOP or an IOP > 18 mmHg on two consecutive follow-up visits, or when patients were required to undergo reoperation. Success rates were determined based on a Kaplan–Meier survival analysis. Results At 3, 6 and 12 months postoperatively, there was a significant postoperative reduction in the IOP (p < 0.001) and in the medications scores (p < 0.001) for both of the groups. In the μLOT-Phaco and iStent-Phaco groups, the probabilities of success at 6 and 12 months were 55.3 and 45.5%, and 48.4 and 45.5% (p = 0.38; log-rank test), respectively. In the iStent-Phaco group, there was a significant decrease in the hyphema. Conclusion Comparable surgical outcomes occurred for both the μLOT and iStent inject W procedures.